Screening for Klebsiella pneumoniae producing carbapenemase in Prato, Italy - Tamara Brunelli; Antonella Conti; Loredana Ortega De Luna; Patrizia Miglietta; Mayra Sosa; Alfredo Ruggeri; Patrizia Casprini; Roberto Degl'Innocenti (Microbiologia Medica, 2014)
In this study, the prevalence of carbapenemase in the area of Prato (Italy), from January 2011 to August 2013, is reported. Samples showing carbapenem resistance were tested for lactamase production with disc diffusion and molecular methods. Totally, 48 out of 1542 patients with K. pneumoniae showed carbapenem resistance (42 KPC 5 MBL and 1 OXA-48).